The science of soil Security and food security (2020)
There is a nexus of seven inter-linked global existential challenges; Soil Security and Food Security are two of these. The established concept of Food Security is well defined and researched, whereas the emerging concept of Soil Security is building its currency globally. Addressing Soil Security provides the means to improve food, fibre and water quality in a sustainable manner, through enhanced soil care and development of best land-management practices. Soil is a fragile resource which is degraded in many parts of the world. The rapidly growing global population has placed further pressure on the soil resource to accommodate increased demand for food, fibre and soil-derived materials. Such pressures are accelerating degradation and so novel approaches are needed. Literature search within this review demonstrated Soil Security and Food Security to be a convergence of disciplines. To truly identify solutions to challenges faced in either realm, an interdisciplinary approach seeking to understand deeper interactions between the two concepts is needed. Driven by this need, our review sought to investigate such interactions between the challenges faced in Soil Security and Food Security. Following assessment of these interactions, four potential solutions were discussed and included sustainable intensification and management, digital agriculture, circularisation and reducing the food demand trajectory through enhanced soil care. Soil Security and Food Security are interconnected concepts which will help facilitate implementation of the above solutions, and so approaches are needed which take this connection into account.